Systematic review and meta‐analysis of sleep quality in inactive inflammatory bowel disease. Issue 11 (29th September 2022) - Barnes, Alex; Mountifield, Réme; Baker, Justin; Spizzo, Paul; Bampton, Peter; Mukherjee, Sutapa
Abstract: Poor sleep in people with inflammatory bowel disease (IBD) has been demonstrated to be prevalent and has been associated with disease activity. This meta‐analysis aimed to assess the prevalence of poor sleep in inactive IBD and in controls by considering cohort and cross‐sectional studies. Electronic databases were searched for publications from inception to 1 November 2021. Poor sleep and IBD activity were defined according to self‐reported subjective sleep measures. A random effects model was used to determine the standardized mean difference between poor sleep in inactive IBD and healthy controls. Publication bias was assessed by funnel plot and Egger's test. Five hundred and nineteen studies were screened with 9 studies included in the meta‐analysis incorporating a total of 729 people with IBD and 508 controls. A random effects model showed a standardized mean difference with poor sleep being more frequent in those with inactive IBD than controls with moderate effect size (Hedge's g 0.41, CI [0.22–0.59]) and no significant heterogeneity. There was no publication bias evident. Poor sleep is more common in individuals with inactive IBD than healthy controls. Further studies should consider potential mechanisms to explain this result, including the role of subclinical inflammation and psychosocial factors that may influence sleep quality in people with IBD. Abstract : This meta‐analysis assessed the prevalence of poor sleep in inactive inflammatory bowel disease and in controls. Poor sleep was found to be more frequent in people with inactive inflammatory bowel disease than controls with moderate effect size. Further studies should consider potential mechanisms to explain this result including the role of subclinical inflammation and psychosocial factors that may influence sleep quality in people with inflammatory bowel disease.